Regulatory Effects of Circular RNAs on Host Genes in Human Cancer - Wang, Xiong; Li, Huijun; Lu, Yanjun; Cheng, Liming (Frontiers in Oncology, 2021)
Circular RNAs (circRNAs) are a class of single-stranded, covalent closed-loop RNAs with tissue-/development-specific expression patterns. circRNAs are stable and play oncogenic or tumor suppressive roles in various aspects of cancer, including tumorigenesis, proliferation, apoptosis, metastasis, invasion, chemo-therapeutic resistance, and prognosis. circRNAs act as miRNA/protein sponges, protein scaffold, or template for translation. Increasing evidence shows circRNAs contribute to cancer progression via modulating the expression or function of their host genes. In this review, we summarize the latest progress in the regulation of host genes by circRNAs in human cancer. The works on circRNAs mediated regulation of host genes enhance us to understand the interaction between circRNAs and their host genes in human cancer.